Primitive Neuroectodermal Tumor (PNET): A Rare Tumor in Differential Diagnosis of Renal Mass in Adolescences - Farzad Allameh; Hamidreza Qashqai; Farideh Mousavi; Ali Asghar Halimi Asl; Amirhossein Rahavian (Case Reports in Clinical Practice, 2017)
A thirteen-year-old boy with a right flank mass and painless gross hematuria is presented. The patient underwent open biopsy and the result was a huge primitive neuroectodermal tumor (PNET) of right kidney. Radical nephrectomy was performed for him and the treatment process continued with systemic chemotherapy.